2023
DOI: 10.1029/2022ms003110
|View full text |Cite
|
Sign up to set email alerts
|

Application of the CNOP‐P Ensemble Prediction (CNOP‐PEP) Method in Evapotranspiration Forecasting Over the Tibetan Plateau to Model Parameter Uncertainties

Abstract: Evapotranspiration (ET) is recognized as an integral component of the regional and global energy and water cycles and is associated with the exchange of mass and energy between atmospheric and land systems (Jung et al., 2010;Trenberth et al., 2009). ET significantly impacts regional and global climate changes (Milly & Dunne, 2016;Scheff & Frierson, 2014). Hence, it is critical for evaluating ET variations to understand land-atmosphere interactions and global climate change. As the highest plateau in the world,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…In the study of Sun et al (2023), just one parameter perturbation was generated by the CNOP-P method to carry out ensemble forecast. In order to assess the differences between the above methods, we implemented ensemble forecasting with the CNOP-PEP method proposed by Sun et al (2023). Numerical results show that the ensemble forecasting skill is highest if all the parameter perturbation ensemble members are generated by the CNOP-PEP method.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the study of Sun et al (2023), just one parameter perturbation was generated by the CNOP-P method to carry out ensemble forecast. In order to assess the differences between the above methods, we implemented ensemble forecasting with the CNOP-PEP method proposed by Sun et al (2023). Numerical results show that the ensemble forecasting skill is highest if all the parameter perturbation ensemble members are generated by the CNOP-PEP method.…”
Section: Discussionmentioning
confidence: 99%
“…From the above description, the CNOP-PEP method is different from that in the study of Sun et al (2023). Just one ensemble member is generated using the CNOP-P method in the study of Sun et al (2023). Their results showed that the CNOP-P-type parameters perturbations helped to improve the ensemble prediction skills of ET.…”
Section: Introduction Of the Cnop-pep Methodsmentioning
confidence: 99%
See 3 more Smart Citations